A Study of Fiqh Al-Muwatanah Juz 1 and 2 and Its Relationship to Muslim and Non-Muslim Relations in Indonesia - Husaeri, Rifki Ahmad; Shahruddin, Mohd Solahuddin (Prodi Magister Sosiologi UIN Sunan Gunung Djati Bandung, 2026)
This study explores the dynamics of relations between Muslims and non-Muslims in Indonesia through the study of the Fiqh Al-Muwatanah book, written by alumni of the Lirboyo Islamic Boarding School in Kediri, as a response to the challenges of nationality, plurality, and religiosity. The study highlights the transformation of classical Islamic jurisprudence (fiqh) views regarding the status of non-Muslims, replacing the term